OPINIONS OF SLOVAK ACADEMIC STAFF AND STUDENTS ON THE PROFESSIONAL COMPETENCES OF ACADEMIC TEACHERS - Kasáčová, Bronislava; Guffová, Daniela (Педагогічна освіта: Теорія і практика. Психологія. Педагогіка., 2020)
The paper is a result of comparative study conducted over the period 2017–2018 within the International Visegrad Fund project No. 21720008. Four countries are included in the project, namely Ukraine, Poland, Czech Republic and Slovak Republic. The opinions of university teachers and students on the competences of academic teachers are investigated and compared within the study. The specifcs of Slovak view and legislation of professional competences are presented in the paper. Moreover, the analysis of data obtained in Slovak universities based on comparison of teachers’ and students’ opinions on academic teachers’ competences are described.